A database of dissolution and precipitation rates for clay-rocks minerals. (April 2015) - Marty, Nicolas C.M.; Claret, Francis; Lassin, Arnault; Tremosa, Joachim; Blanc, Philippe; Madé, Benoit; Giffaut, Eric; Cochepin, Benoit; Tournassat, Christophe
Highlights: The present work aims at proposing a compilation of kinetic parameters. The selection of minerals is currently limited to clay rich rocks and cements. Selected rate parameters have been used to simulate independent experiments. Database is available in different formats (PhreeqC, CrunchFlow, ToughReact). Abstract: Many geoscientific fields use reactive transport codes to set up and interpret experiments as well as to understand natural processes. Reactive transport codes are also useful to give insights in the long term evolution of systems such as radioactive waste repositories or CO2 storage sites, for which experiments cannot reach the targeted time scale nor the dimension of those systems. The consideration of kinetic reaction rates is often required to reproduce correctly the geochemical and transport processes of interest. However, kinetic data are scattered in the literature, making data and selection a tedious task. Kinetic parameters on a single system are also highly variable depending on data choice, interpretation and chosen kinetic modelling approaches, thus making inter-comparison of modelling studies difficult. The present work aims at proposing a compilation of kinetic parameters to overcome part of above cited problems. The proposed selection was done (i) to ensure consistency of data selection criteria and data treatment and (ii) to ease the use of common kinetic parameters that are independent of the chosen geochemical modelling code. For those two reasons, the kinetic formalism of the transition state theory (TST) was chosen. The selection of minerals is currently limited to those present in clay rich rocks and cements, reflecting the effort made at predicting the evolution of radioactive waste underground storage systems. Still, the proposed compilation should also be useful for other applications such as CO2 sequestration.